Subthalamic Nucleus: Neuroanatomical Review - Magalhães, Marcelo José Silva de; Reis, Claudiojanes dos; Sousa, Juliana Rabelo da Silva; Marques, Victória Souza; Gonçalves, Tayná Cardoso; Ribeiro, Iara Cristina Vieira; Cardoso, Leide Daiana Silveira; Guimarães, Victor Caribé Crosland; Marques, Frederico Gustavo de Souza; Pereira, Sarah Dias (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Discovered in 1865 by Jules Bernard Luys, the subthalamic nucleus is a set of small nuclei located in the diencephalon, inferior to the thalamus and superior to the substantia nigra, that can be visualized in a posterior coronal section. Histologically, it consists of neurons compactly distributed and filled with a large number of blood vessels and sparse myelinated fibers. This review presents an analysis of this anatomical region, considering what is most recent in the literature. Subthalamic neurons are excitatory and use glutamate as the neurotransmitter. In healthy individuals, these neurons are inhibited by nerve cells located in the side globus pallidus. However, if the fibers that make up the afferent circuit are damaged, the neurons become highly excitable, thus causing motor disturbances that can be classified as hyperkinetic, for example ballism and chorea, or hypokinetic, for example Parkinson disease (PD). The advent of deep brain stimulation has given the subthalamic nucleus great visibility. Studies reveal that the stimulation of this nucleus improves the motor symptoms of PD.
Keywords: subthalamic nucleus; efferent pathways; chorea; Parkinson disease